A Case of Large Phyllodes Tumor Causing "Rupture" of the Breast: A Unique Presentation. (14th May 2013) - Nabi, Junaid; Akhter, S. M. Quamrul; Authoy, Fatema N.
Abstract : Introduction . Phyllodes tumors are rare fibroepithelial tumors which constitute less than 1% of all known breast neoplasms. The importance of recognizing these tumors lies in the need to differentiate them from fibroadenomas and other benign breast lesions to avoid inappropriate surgical management. We report a case of large phyllodes tumor which caused rupture of the breast and presented as an external fungating breast mass, a presentation which is exceedingly rare. Case Presentation . A 32-year-old female presented with a 1-year history of a mass in her right breast and eruption of the mass through the skin for the last 3 months. On physical examination, an ulcerated, irregular, and nodular mass measuring 9 × 8 cms was found hanging in the lower and outer quadrant of the right breast. Ultrasonography revealed an exophytic mass with heterogeneous echotexture and vascularity. Under general anesthesia, the tumor was excised. The resected specimen was 9 . 5 × 8 . 5 × 4.5 cm in size and the tumor was not invasive to the surrounding tissues. Histological examination confirmed a benign case of Phyllodes tumor. Conclusion . Clinicians should be aware of the myriad ways in which Phyllodes can present. A rapidly growing breast mass in a female should raise strong suspicion for Phyllodes. It is necessary to differentiate it from fibroadenomas to avoid inappropriate surgical management which may lead to local recurrence.